Analisis Nilai Ketidakpastian dan Faktor Kalibrasi pada Alat Ukur Radiasi di Balai Pengamanan Fasilitas Kesehatan Surabaya: Kardianto, Kurnia Hastu Kristanti, Kandi Ayu Tiswati, dan Yanurita Dwihapsari - Kardianto Kardianto; Kurnia Hastu Kristanti Kurnia Hastu Kristanti; Kandi Ayu Tiswati Kandi Ayu Tiswati; Yanurita Dwihapsari Yanurita Dwihapsari (Jurnal Fisika dan Aplikasinya, 2019)
Radiation measurement calibration for ionizing radiation instrument is a compulsory procedure in hospitals and health facilities according to Minister of Health Regulation No. 54/2015. This study observed radiation measurement calibration in health facilities across East Java and was conducted at Surabaya Health Facilities Security Center (Balai Pengamanan Fasilitas Kesehatan Surabaya). The uncertainty and calibration factor were measured and calculated on 20 analog pocket dosimeters, 20 digital pocket dosimeters and 10 gamma surveymeters with reference sources of Cs-137. From 40 pocket dosimeters and 10 gamma surveymeters, only 1 analog pocket dosimeter was not feasible to use because its calibration factor was outside the allowed standard value.